2020
DOI: 10.1128/msystems.00687-19
|View full text |Cite
|
Sign up to set email alerts
|

From Modules to Networks: a Systems-Level Analysis of the Bacitracin Stress Response in Bacillus subtilis

Abstract: Bacterial resistance against antibiotics often involves multiple mechanisms that are interconnected to ensure robust protection. So far, the knowledge about underlying regulatory features of those resistance networks is sparse, since they can hardly be determined by experimentation alone. Here, we present the first computational approach to elucidate the interplay between multiple resistance modules against a single antibiotic and how regulatory network structure allows the cell to respond to and compensate fo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
2

Relationship

4
1

Authors

Journals

citations
Cited by 10 publications
(18 citation statements)
references
References 40 publications
(65 reference statements)
3
15
0
Order By: Relevance
“…However, any attempts at changing the concentration of lipid II in the cell, e.g., by deletion of penicillin-binding proteins (PBPs), have so far been unsuccessful. This is presumably due to redundancy between multiple PBPs and is also consistent with our mathematical model, which showed that the large UPP pool in the cycle can act as an effective buffering reservoir to compensate for interference with the much smaller lipid II pool (26,27).…”
Section: Resultssupporting
confidence: 88%
See 4 more Smart Citations
“…However, any attempts at changing the concentration of lipid II in the cell, e.g., by deletion of penicillin-binding proteins (PBPs), have so far been unsuccessful. This is presumably due to redundancy between multiple PBPs and is also consistent with our mathematical model, which showed that the large UPP pool in the cycle can act as an effective buffering reservoir to compensate for interference with the much smaller lipid II pool (26,27).…”
Section: Resultssupporting
confidence: 88%
“…It also explains the observations on reduced resistance upon overproduction of HPP in the cell, where some of BceAB's transport activity is likely invested in the futile removal of bacitracin from HPP rather than UPP (14). It is consistent with the data reported here and previously (9,27) that the factor determining the transport activity of BceAB is the concentration of UPP-BAC complexes in the cell. Target protection of cell wall synthesis also offers a plausible explanation for the use of transporters in resistance against cell wall-active antibiotics in Gram-positive bacteria.…”
Section: Attempted Depletion Of Upp Affects Transport Activity On a Gsupporting
confidence: 92%
See 3 more Smart Citations